2016
DOI: 10.1111/jop.12455
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of curcumin on head and neck carcinoma: a systematic review

Abstract: This systematic review demonstrated that curcumin is effective on HNSCC cell proliferation and survival, reinforcing the currently available evidence that curcumin could be an adjuvant drug in HNSCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 66 publications
5
30
0
Order By: Relevance
“…However, the activities of caspase-3 and caspase-9 were dramatically enhanced in CAR cells prior to treatment with cetuximab in combination with curcumin; or with exposure only to curcumin. The present results are also consistent with previous studies ( 26 , 31 ) showing that curcumin is effective against various types of cancer via intrinsic apoptotic function. Although curcumin possesses powerful biological activities, it does not reach the criteria of a good drug candidate because it lacks adequate water solubility and high bioavailability, and undergoes rapid in vivo metabolism ( 60 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the activities of caspase-3 and caspase-9 were dramatically enhanced in CAR cells prior to treatment with cetuximab in combination with curcumin; or with exposure only to curcumin. The present results are also consistent with previous studies ( 26 , 31 ) showing that curcumin is effective against various types of cancer via intrinsic apoptotic function. Although curcumin possesses powerful biological activities, it does not reach the criteria of a good drug candidate because it lacks adequate water solubility and high bioavailability, and undergoes rapid in vivo metabolism ( 60 ).…”
Section: Discussionsupporting
confidence: 94%
“…The anticancer activities of curcumin are attributable to its anti-proliferative, anti-angiogenic, anti-metastatic, pro-apoptotic and autophagic characteristics ( 21 25 ). In vitro studies reported that curcumin inhibited cell proliferation in various oral cancer cell lines, including CAL 27, 1483, SCC-1, SCC-9, KB, SAS and SCC15 ( 26 ). Curcumin also suppressed EGFR expression and its downstream signaling molecules (NF-κB, JNK, p38 and ERK) which are vital for oral cancer pathogenesis ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effects of turmeric and curcumin on the oral cavity, results were positive when it was applied as relief for tooth pain, cavity sealant, subgingival irrigator, and treatment for aphthous and potentially malignant lesions (Grover, Deswal, & Bhardwaj, 2015;Nagpal & Sood, 2013). Curcumin also inhibited tumor growth and cell viability and induced cytotoxicity, cell cycle arrest, and apoptosis in in vitro and in vivo head and neck carcinoma models, as observed by our research group in a previous systematic review (Borges et al, 2017). When tested in cutaneous radiation toxicity, curcumin was effective in reducing the severity of radiation dermatitis and moist desquamation in cancer patients (Palatty et al, 2014;Ryan et al, 2013;Vaughn, Branum, & Sivamani, 2016).…”
Section: Introductionsupporting
confidence: 71%
“…Combined treatment with curcumin and various anticancer drugs, such as 5‐FU and cisplatin, has been shown to improve efficacy and reduce toxicity . When utilized in HNSCC, the anticarcinogenic properties of curcumin include induction of apoptosis, cell cycle arrest, radiosensitivity, and chemotherapy sensitization . Dual treatment with both curcumin and metformin has been reported in hepatocellular carcinoma, pancreatic cancer cells, and breast cancer with the results suggesting synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] When utilized in HNSCC, the anticarcinogenic properties of curcumin include induction of apoptosis, cell cycle arrest, radiosensitivity, and chemotherapy sensitization. 27 Dual treatment with both curcumin and metformin has been reported in hepatocellular carcinoma, 28 pancreatic cancer cells, 29 and breast cancer 30 with the results suggesting synergistic effects. Combined treatment with metformin and curcumin is also thought to enhance chemoprevention properties, in vitro and in vivo, in oral cancer.…”
Section: Introductionmentioning
confidence: 99%